Amino acid identification and protein content determination of Locusta migratoria manilensis Meyen (Family Locustidae) - Smith, Allan T.
The total Nitrogen content of dried Locusta migratoria was determined using Kjeldahl method. Three determinations were made and the values obtained were 6.65%, 5.91%, and 8.91%, giving an average of 7.15%. The percentage deviation for each trial was 6.99%, 17.34% and 24.62%, respectively. The non-protein Nitrogen content (NPN) was also determined and the values obtained were: 1.90% and 1.71%, giving an average of 1.80%. The percent deviation for each trial was 5.56% and 5.00%, respectively. The average NPN content was subtracted from the total Nitrogen content and the result was multiplied by 6.25 to get the percentage protein content. The value obtained was 33.43%.